Morphometry of subaerial shield volcanoes and glaciovolcanoes from Reykjanes Peninsula, Iceland: Effects of eruption environment - Pedersen, G. B. M.; Grosse, Pablo (Journal of Volcanology and Geothermal Research)
We present a morphometric study of 33 basaltic volcanic edifices from the Reykjanes Peninsula, Iceland, using a 20 m resolution digital elevation model (DEM). Slope values distinguish subaerial from intraglacial eruption environments, with glaciovolcanic edifices having average slope values that are > 5° higher than subaerial shields. The 26 analyzed glaciovolcanic edifices are separated into 3 groups based on size, and are also categorized following the new classification scheme of tuyas by Russell et al. (2014), into 15 tindars, 1 conical tuya, 3 flat-topped tuyas and 7 complex tuyas. The glaciovolcanic edifices show a continuum of landforms ranging from small elongated tindars to large equidimensional flat-topped tuyas. The smaller edifices (< 0.01 km3) are all tindars and the larger edifices (> 0.1 km3) are flat-topped tuyas. The mid-sized edifices (0.01–0.1 km3) show a wide variety of shapes and classify either as tindars or as complex tuyas, with only one edifice classifying as a conical tuya. Edifice elongation tends to decrease with volume, suggesting that small edifices are primarily fissure controlled, whereas larger edifices are mainly controlled by a central vent. The mid-sized complex tuyas are transitional edifices, suggesting that some intraglacial eruptions start as fissure eruptions that subsequently concentrate into one or more central vents, whereas the mid-sized tindars suggest a sustained fissure eruption. There is a tectonic control on the orientation of the edifices evidenced by a strong correlation between edifice elongation azimuth and mapped faults and fractures. Most edifice elongations cluster between 020° and 080°, coinciding with the strike of normal faults within and at the boundary of regional volcanic systems, but some edifices have elongations that correlate with N–S striking book-shelf faults. This implies that intraglacial eruptions are controlled by pre-existing pathways in the crust, as has been previously observed for subaerial fissure eruptions. In terms of ...